Effects of feed quality and quantity on growth, early maturation and smolt development in hatchery‐reared landlocked Atlantic salmon Salmo salar. Issue 4 (October 2014) - Norrgård, J. R.; Bergman, E.; Greenberg, L. A.; Schmitz, M.
<x xml:space="preserve">Abstract</x> The effects of feed quality and quantity on growth, early male parr maturation and development of smolt characteristics were studied in hatchery‐reared landlocked Atlantic salmon Salmo salar. The fish were subjected to two levels of feed rations and two levels of lipid content from first feeding until release in May of their second year. Salmo salar fed high rations, regardless of lipid content, grew the most and those fed low lipid feed with low rations grew the least. In addition, fish fed low lipid feed had lower body lipid levels than fish fed high lipid feed. Salmo salar from all treatments showed some reduction in condition factor (K) and lipid levels during their second spring. Smolt status was evaluated using both physiological and morphological variables. These results, based on gill Na+, K+‐ATPase (NKA) enzyme activity, saltwater tolerance challenges and visual assessments, were consistent with each other, showing that S. salar from all treatments, except the treatment in which the fish were fed low rations with low lipid content, exhibited characteristics associated with smolting at 2 years of age. Sexually mature male parr from the high ration, high lipid content treatment were also subjected to saltwater challenge tests, and were found to be unable to regulate plasma sodium levels. The proportion of sexually mature male parr was reduced when the fish were fed low feed rations, but was not affected by the lipid content of the feed. Salmo salar fed low rations with low lipid content exhibited the highest degree of severe fin erosion.